Translanguaging Practices in Language Classrooms - Maya Marsevani; Hana Julia S (International Journal of Research in Education, 2023)
This research aim at examining students’ perceptions regarding the use of tranlanguaging in language classroom. There were 29 students in a university level involved in this research. Mix methods was used to gain data in which observation, questionnaire, and interview were implemented. Observations analyzed qualitatively by using descriptive analysis in detail information. The questionnaire was further analyzed by calculating percentages in Likert scale questionnaire. For interview section, researchers developed the question based on students answers from google form and transcribed all information and responses into English language. The findings show that students assess translanguaging from 2 aspects, positive and negative. Although they have a positive view of translating in certain situations, they do not often use this pedagogy because it is considered less efficient. This research emphasized that students can gain the good impact of translanguaging if they have a deep understanding how to practice it correctly in language classroom.